Moderating Effect of Supply Chain Dynamic Capabilities on the Relationship of Sustainable Supply Chain Management Practices and Organizational Sustainable Performance: A Study on the Restaurant Industry in Indonesia - Dewi Budhiartini Yuli Isnaini; T Nurhaida; Ikbar Pratama (International Journal of Supply Chain Management, 2020)
The sustainable supply chain management (SSCM) is a fairly new topic that has become a superior attention for the researchers recently. The current study is investigated empirically moderating effect of Supply chain dynamic capabilities (SCDC) on the relationship of SSCM practices and organizational sustainable performance (OSP) indicators namely; “economic performance, environmental performance, social performance” in the restaurant industry of Indonesia. For this purpose, data was collected from the 210 supply chain managers by using the simple random sampling technique which yield a 78% response rate. For data analysis Smart PLS 3 software and PLS Structural Equation Modeling (SEM) approach was employed. The SEM analysis has shown, SSCM practices has a significant association with the OSP indicators. Moreover, the findings of the current study also shown that SCDC is significantly moderates on the relationship of SSCM practices and OSP in the restaurant industry of Indonesia. This shows that SCDC is considered to be an important contribution of the study. The current research also contributes a body of knowledge in the way of theoretical and practical implications. The study limitations and future directions are also discussed at last of the study.